Matrix cracking initiation, propagation and laminate failure in multiple plies of general symmetric composite laminates. (September 2020) - Hajikazemi, M.; McCartney, L.N.; Van Paepegem, W.
Abstract: This paper formulates an analytical model based on intrinsic material properties to predict ply cracking initiation and propagation in multiple plies and its impact on laminate strength in general symmetric laminates (possibly made of thin-plies) under combined triaxial normal loads and in-plane and out-of-plane shear loads while the effect of thermal residual stresses and statistical distribution of fracture energies are considered. To do so, a novel complete homogenization technique combined with recently developed accurate stress transfer models is implemented in conjunction with multi-axial energy-based failure criteria, Monte Carlo type of simulation and a strain-based fiber failure criterion. The model predictions show very good agreement with experimental results.